Association between genetic polymorphisms of miRNAs (miR-8079 and miR-5007) and susceptibility of chronic obstructive pulmonary disease in Chinese people. (November 2021) - Xu, Dan; Jing, Jing; Li, Zheng; Wang, Jing; Jiang, Min; Meng, Ting
Abstract: Background: Chronic obstructive pulmonary disease (COPD) has been recognized as a heterogeneous disease, which is caused by biological heterogeneity. The purpose of our study is to determine the association between the single nucleotide polymorphisms (SNPs) of miRNAs (miR-8079 and miR-5007) and the susceptibility to COPD in Chinese population. Methods: We conducted a 'case-control' study involving 315 COPD patients and 314 healthy individuals. Three SNPs of miR-8079 (rs9533803, rs9525927, rs7981875) and three SNPs of miR-5007 (rs9527345, rs2252932, rs2997119) were selected, then we used logistic regression to analyze the association between candidate SNPs and COPD susceptibility under different genetic models. Multi-factor dimensionality reduction (MDR) was used to analyze the interaction of "SNP-SNP" in COPD risk studies. Finally, we used univariate and ANOVA to analyze the differences in clinical characteristics among different genotypes. Results: Our results showed that miR-8079-rs9525927 was significant associated with COPD susceptibility whether in overall and stratified analysis. miR-5007-rs2997119 was associated with the increased risk of COPD in women under multiple genetic models; miR-8079-rs9525927 and miR-5007-rs9527345 had a certain association with clinical indicator Fev_1 of COPD patients; rs9527345 or rs2252932 on miR-5007 was associated with the risk of COPD with wheezing dyspnea or wheezing. Conclusion: Our results suggested that the genetic polymorphisms of miR-8079 or miR-5007 were potentially associated with COPD risk, of which miR-8079-rs9525927 was more prominent. Highlights: The genetic polymorphisms of miR-8079 or miR-5007 were associated with COPD risk, miR-8079-rs9525927 was more prominent. Our study is the first to find that the SNPs of miR-8079 or miR-5007 have a certain association with the COPD risk. Our study provide a new data supplement for the association study between miRNA SNPs and COPD susceptibility.